Multifunctional human serum albumin-therapeutic nucleotide conjugate with redox and pH-sensitive drug release mechanism for cancer theranostics. Issue 16 (15th August 2017) - Lisitskiy, Vladimir A.; Khan, Hamda; Popova, Tatyana V.; Chubarov, Alexey S.; Zakharova, Olga D.; Akulov, Andrey E.; Shevelev, Oleg B.; Zavjalov, Evgenii L.; Koptyug, Igor V.; Moshkin, Mikhail P.; Silnikov, Vladimir N.; Ahmad, Saheem; et al.
Graphical abstract: Abstract: We report on the synthesis and properties of a new multimodal theranostic conjugate based on an anticancer fluorinated nucleotide conjugated with a dual-labeled albumin. A fluorine-labeled homocysteine thiolactone has been used as functional handle to synthesize the fluorinated albumin and couple it with a chemotherapeutic agent 5-trifluoromethyl-2′-deoxyuridine 5′-monophosphate (pTFT). The conjugate allows for direct optical and 19 F magnetic resonance cancer imaging and release of the drug upon addition of glutathione. Interestingly, the pTFT release from albumin conjugate could only be promoted by the increased acidity (pH 5.4). The in vitro study and primary in vivo investigations showed stronger antitumor activity than free pTFT.